Cluster randomised controlled trial of a guided self-help mental health intervention in primary care. Issue 2 (27th February 2019) - Mathieson, Fiona; Stanley, James; Collings, Catherine (Sunny); Tester, Rachel; Dowell, Anthony
Abstract : Objectives: To ascertain whether an ultrabrief intervention (UBI) improves mental health outcomes for patients in general practice with mild-to-moderate mental health concerns. Trial design: Two-arm cluster randomised controlled trial. Methods: Participants: general practitioners (GPs) were invited based on working in a participating general practice. Patients were eligible to participate if aged 18–65 years, scored ≤35 on the Kessler-10 (K10) and if meeting local mental health access criteria (based on age, low income or ethnic group). Interventions: intervention arm GPs were trained on the UBI approach, with participating patients receiving three structured appointments over 5 weeks. GPs randomised to practice as usual (PAU) did not receive training, and delivered support following their existing practice approaches. Outcome measures: primary outcome was patient-level K10 score at 6 months postrecruitment. Randomisation: GP practices were randomised to UBI training or PAU at the start of the study. Blinding: GPs were not blinded to group assignment. Results: Numbers randomised: 62 GPs (recruiting 85 patients) were randomised to UBI, and 50 to PAU (recruiting 75 patients). Numbers analysed: 31 GPs recruited at least one patient in the UBI arm (70 patients analysed), and 21 GPs recruited at least one patient in the PAU arm (69 patients analysed). Outcome: K10 scores from an intention-to-treat analysis were similar in UBI and PAU arms, with a wide CI (mean adjusted K10 difference=1.68 points higher in UBI arm, 95% CI −1.18 to 4.55; p=0.255). Secondary outcomes were also similar in the two groups. Conclusions: the UBI intervention did not lead to better outcomes than practice as usual, although the study had lower than planned power due to poor recruitment. The study results can still contribute to the continuing debate about brief psychological therapy options for primary care and their development. Trial registration number: ACTRN12613000041752; Pre-results.